Mecanismos prosencefálicos e da área rostroventrolateral do bulbo no controle de respostas cardiovasculares em ratos acordados - Gomide, Joelma Maria Cardoso (2013)
The rostroventrolateral medulla (RVLM) is a main central area of origin of sympathetic premotor neurons in the central nervous system (CNS) and has an important role in the generation and maintenance of sympathetic vasomotor tone. The RVLM receives both excitatory and inhibitory influences from different regions of the CNS. Recent results from our laboratory suggest that the activity of forebrain cholinergic and angiotensinergic mechanisms and anteroventral region of the third ventricle (AV3V) is important for the pressor response produced by injection of the excitatory amino acid glutamate in the RVLM. Intracerebroventricular (icv) injection of carbachol (cholinergic agonist) or angiotensin II (ANG II) causes pressor responses dependent on sympathetic activation and vasopressin secretion that are abolished by lesions of the AV3V region. Studies in anesthetized rats suggested that changes in fluid-electrolyte balance, particularly in rats with access to only normal chow and 0.9% NaCl for 14 days, increases sympathetic activity and blood pressure in response to injections of glutamate into the RVLM. In the present study, we investigated the cardiovascular responses produced by injection of glutamate, acetylcholine, GABA and angiotensin II in the RVLM in unanesthetized rats after 24 h water deprivation or access to only normal chow and 0.9% NaCl for 14 days. In this last protocol it was also tested the effects of different doses of glutamate (0.1, 1, 3 and 5 nmol/100 nl) injected into the RVLM. Basal mean arterial pressure (MAP) and heart rate (HR) in rats with 24 h of water deprivation (108 +- 2 mmHg and 354 +- 17 bpm, respectively) or rats treated with normal chow and 0.9% NaCl for 14 days (115 +- 2 mmHg and 359 +- 17 bpm, respectively) were not different from those of control animals (113 +- 2 mmHg and 383 +- 16 bpm, respectively). Changes in MAP of animals with 24 h water deprivation were not different from those observed in control animals after injection into the RVLM of glutamate (5 nmol/100 nl) (51 +- 3 mmHg, vs. controls: 55 +- 4 mmHg), acetylcholine (10 nmol/100 nl) (22 +- 9 mmHg, vs. controls: 15 +- 12 mmHg), angiotensin II (200 ng/100 nl) (41 +- 5 mmHg, vs. controls: 50 +- 6 mmHg) or GABA (1 nmol/100 nl) (-19 +- 3 mmHg, vs. controls: -19 +- 3 mmHg). In animals that had access to 0.9% NaCl for 14 days, the changes in MAP were also similar to control animals after injection into the RVLM of glutamate (42 +- 7 mmHg, vs. controls: 46 +- 16 mmHg), acetylcholine (31 +- 3 mmHg, vs. controls: 26 +- 2 mmHg), angiotensin II (53 +- 4 mmHg, vs. controls: 46 +- 8 mmHg) or GABA (-22 +- 5 mmHg vs. controls: -17 +- 4 mmHg). In rats with access to 0.9% NaCl for 14 days we did not observe differences in the changes in MAP produced by injection of glutamate into the RVLM at doses of 0.1 nmol/100 nl (11 +- 1 mmHg, vs. controls: 10 +- 4 mmHg), 1 nmol/100 nl (17 +- 6 mmHg, vs. controls: 14 +- 4 mmHg), 3 nmol/100 nl (24 +- 9 mmHg, vs. controls: 43 +- 11 mmHg) or 5 nmol/100 nl (43 +- 6 mmHg, vs. controls: 56 +- 6 mmHg). The HR variations produced by the different treatments in the RVLM in control rats, rats with 24 h of water deprivation or those that had access to 0.9% NaCl for 14 days were also similar. Unlike the results in the literature with anesthetized rats, the present results suggest that the access to normal chow and 0.9% NaCl for 14 days does not modify the cardiovascular responses produced by the injection of different doses of glutamate, acetylcholine, ANG II or GABA into the RVLM in unanesthetized rats. The same is true for unanesthetized rats with 24 h water deprivation. Another objective of this study was to investigate the cardiovascular responses produced by injection of glutamate into the RVLM in awake rats pretreated with either carbachol (cholinergic agonist) or ANG II injected into the lateral ventricle (LV). Basal MAP and HR of the animals were 117 +- 4 mmHg and 400 +- 17 bpm, respectively. The pressor response produced by injection of glutamate (5 nmol/100 nl) into the RVLM increased after pretreatment with carbachol (4 nmol/1 £gl) or Ang II (50 ng/1 £gl) injected icv (59 +- 3 and 68 +- 5 mmHg, respectively) compared with the control responses produced by glutamate injection in the RVLM combined with icv injection of vehicle (37 +- 3 mmHg). The pressor responses produced by the injection of carbachol or ANG II icv (which reached a maximum of 56 +- 3 and 44 +- 3 mmHg, respectively) were already reduced (9 +- 2 and 6 +- 3 mmHg, respectively) at the time of injection glutamate into the RVLM (20 min after icv injection). There was no difference in the changes in HR that occurred after the injection of carbachol or ANG II into the LV or glutamate injected into the RVLM alone or combined. These results suggest that central cholinergic or angiotensinergic activation facilitates the pressor response produced by RVLM glutamatergic activation. Moxonidine (£\2 adrenergic/imidazole receptor agonist), used as antihypertensive, reduces sympathetic discharges by central action. Thus, we investigated the effect of previous injection of moxonidine into the RVLM on the cardiovascular responses produced by glutamate injection in the same area. Basal MAP and HR of the animals were 112 +- 4 mmHg and 393 +- 30 bpm, respectively. The previous injection of moxonidine (5 nmol/100 nl) into the RVLM reduced the pressor response produced by the injection of glutamate (5 nmol/100 nl) into the RVLM (23 +- 3 mmHg, vs. after vehicle: 45 +- 6 mmHg) without significant changes in the bradycardic response (-7 +- 18 bpm, vs. after vehicle: -28 +- 15 bpm). The results suggest that activation of £\2 adrenergic/imidazole receptors by the injection of moxonidine into the RVLM attenuates the pressor response resulting from sympathetic activation produced by glutamatergic stimulation of this area. Finally we investigated the cardiovascular responses produced by the injection of carbachol into the LV in rats treated with moxonidine injected bilaterally into the RVLM combined or not with vasopressinergic antagonist (AVP) injected intravenously (iv). Baseline MAP and HR of the animals that were treated with carbachol in the LV combination or not with the antagonist of AVP iv + moxonidine into the RVLM were 118 +- 3 mmHg and 404 +- 12 bpm, respectively. Bilateral injections of moxonidine (5 nmol/100 nl) into the RVLM in these rats caused a reduction in MAP when compared with the pre-injection values or controls. HR reduction was also observed after injections of moxonidine into the RVLM when compared to control. Previous injections of moxonidine (5 nmol/100 nl) into the RVLM reduced the initial pressor response (2 minutes) produced by the injection of carbachol (4 nmol/1 £gl) into the LV (21 +- 4 mmHg, vs. vehicle 40 +- 2 mmHg), whereas later (8 to 18 min after the injection of carbachol) occurred a potentiation of the pressor response to carbachol (63 +- 4 mmHg, vs. vehicle 44 +- 2 mmHg). The prior iv injection of the vasopressin V1 receptor antagonist (10 mg/kg body weight) reduced the late pressor response (8 to 18 min) produced by the injection of carbachol (4 nmol/1 £gl) in the rats treated with LV injections of moxonidine (5 nmol/100 nl) into the RVLM (8': 22 +- 3 mmHg; 10': 19 +- 3 mmHg; 12': 18 +- 3 mmHg; 14': 18 +- 3 mmHg; 16': 14 +- 3 mmHg; 18': 12 +- 3 mmHg) or vehicle treated in RVLM (8': 20 +- 3 mmHg; 10': 16 +- 3 mmHg; 12': 14 +- 3 mmHg; 14': 13 +- 3 mmHg; 16': 12 +- 3 mmHg; 18': 12 +- 3 mmHg). In rats treated with AVP antagonist the initial pressor response (2 minutes) was also reduced in the groups receiving moxonidine in the RVLM (17 +- 3 mmHg) or vehicle in RVLM the (29 +- 4 mmHg). There was no difference in the late response to carbachol of rats receiving injections of vehicle or moxonidine into the RVLM combined with vasopressin antagonist iv. The HR changes that occurred after the injection of carbachol into the LV combined with moxonidine or vehicle injected into the RVLM in rats receiving or not vasopressin antagonist iv were similar. The peak pressor response to carbachol injected into the LV of rats treated with moxonidine injected into the RVLM which was higher (63 +- 4 mm Hg) than that of vehicle-treated rats in RVLM (43 +- 2 mmHg) was reduced to similar values in rats with blockade of vasopressin V1 receptor treated with moxonidine (26 +- 2 mmHg) or vehicle in RVLM (32 +- 2 mmHg). Thus, the present results suggest that the late increase in the pressor response produced by injections of carbachol icv in rats treated with moxonidine in RVLM is due to increased secretion of vasopressin.